Системи сіток у Figma : створення власної сітки для адаптивного дизайну - Івах, Є. Ф.; Щукіна, Л. Б. (ХНУРЕ, 2025)
This work is dedicated to the critical role of grid systems in UI/UX design and their significant impact on adaptive layouts. Grid structures help organize space, maintain visual balance, and greatly improve usability across various de vices. The paper delves into the main types of grids, including column, modular, and baseline grids, thoroughly explaining their diverse applications in modern web and mobile interfaces. The article also highlights the numerous benefits of creating a custom grid in Figma, ensuring flexibility, structured alignment, and optimized user experience for scalable and visually harmonious interfaces.
Keywords: Figma; адаптивний дизайн